The impact of body mass index on dosimetric quality in low-dose-rate prostate brachytherapy - Echevarria, Michelle I.; Naghavi, Arash O.; Venkat, Puja S.; Abuodeh, Yazan A.; Chevere, Carlos; Yamoah, Kosj (Journal of Contemporary Brachytherapy, 2016)
Purpose : Low-dose-rate (LDR) brachytherapy has been established as an effective and safe treatment option for men with low and intermediate risk prostate cancer. In this retrospective analysis, we sought to study the effect of body mass index (BMI) on post-implant dosimetric quality. Material and methods : After institutional approval, records of patients with non-metastatic prostate cancer treated in Puerto Rico with LDR brachytherapy during 2008-2013 were reviewed. All patients were implanted with 125I seeds to a prescription dose of 145 Gy. Computed tomography (CT) based dosimetry was performed 1 month after implant. Patients with at least 1 year of prostate-specific antigen (PSA) follow-up were included. Factors predictive of adequate D90 coverage (≥ 140 Gy) were compared via the Pearson χ2 or Wilcoxon rank-sum test as appropriate. Results : One-hundred and four patients were included in this study, with 53 (51%) patients having a D90 ≥ 140 Gy. The only factor associated with a dosimetric coverage detriment (D90 < 140 Gy) was BMI ≥ 25 kg/m2 (p = 0.03). Prostate volume (p = 0.26), initial PSA (p = 0.236), age (p = 0.49), hormone use (p = 0.93), percent of cores positive (p = 0.95), risk group (p = 0.24), tumor stage (p = 0.66), and Gleason score (p = 0.61) did not predict D90. Conclusions : In this study we show that BMI is a significant pre-implant predictor of D90 (< 140 Gy vs. ≥ 140 Gy). Although other studies have reported that prostate volume also affects D90, our study did not find this correlation to be statistically significant, likely because all of our patients had a prostate volume 140 Gy.